Sistema de medição de potência óptica LoraWan - Nascimento, Danillo Fernandes (2024)
According to the National Telecommunications Agency (ANATEL), in a report released in 2022, it detailed that around 63% of fixed broadband connections used fiber optic networks for connection. This report demonstrates the constant expansion of fiber optic networks in Brazil. The high demand for optical networks means that internet providers face challenges in delivering a quality service that promotes a positive customer experience. As a result, companies in the sector have been looking for solutions to solve problems in connecting optical networks. There are techniques and tools that enable providers to monitor the network connection, carry out speed tests, promote customer service and carry out preventive maintenance. One of these tools is the Optical Power Meter (OPM), a device capable of measuring optics in fiber optic networks. This work develops an optical power measurement system for passive fiber optic networks. It consists of a device responsible for measuring the power of the optical fiber, and a gateway that sends the power data to a server. Through laboratory tests, the system proved capable of measuring a power range of -42.87 dBm and 5.42 dBm. Communication between the device and the gateway is carried out using the LoRaWAN communication protocol, making the system integrated with the Internet of Things (IoT).